Understanding the links between agriculture and health: Agriculture, food, and health: perspectives on a long relationship - Lang, Tim (International Food Policy Research Institute, 2006)
Agriculture produces food fundamental for human health. It therefore seems obvious that agriculture, food, and health are related! Agriculture affects whether people have enough food to eat, whether it is of sufficient nutritional value, and whether it is safe, all of which affect human health. But it is not so simple: history has taught that there are different ways of looking at the relationships between agriculture, food, and health. Agricultural connections to food and health are mediated by the natural environment, human culture, and technological change. The challenge today of how to achieve equitable food production that delivers optimum nutrition for health requires an ever better understanding of the interplay between agriculture and environment, culture, and technical capacity, and how it has changed over time... there is growing recognition among all stakeholders that: current institutions do not yet adequately link policy demands across levels of governance: global, regional, national, and local; the coincidence of over-, under-, and malconsumption within societies is likely to remain and possibly grow, particularly if current global economic trends continue; nutrition will have to play a more direct part in framing farm policy and practice; agriculture will face renewed pressure to deliver, via sustainable methods, not just more food, but better-quality and health-enhancing foods; and market mechanisms need a stronger push to link health, environment, and food systems in ways that are equitable, both within and between nations, while prioritizing public health.